Fair trade - Lee, Sharon, 1952-; Miller, Steve, 1950 July 31- (Lee, Sharon, 1952- Liaden universe., 2023)
"Jethri Gobelyn has risen far: from despised youngest on a Terran family Loop ship to second trader on premier Liaden tradeship Elthoria under the guidance of his unlikely foster-mother Norn ven'Deelin Clan Ixin. Master Trader ven'Deelin has taught Jethri much, and she expects great things from him. Indeed, one might say she demands them. Jethri has inherited a mission from his father, a plan that will allow family Loop ships like the one he grew up on to survive the encroachment of Rostov's Dust. In this, he's backed by several prominent Looper families who are scheduled to meet and plan at the South Axis Trade Fair. In what seems to be a fortunate pairing of missions, Master Trader ven'Deelin sees Jethri become lead trader on his own small ship, which is scheduled to arrive at the South Axis Fair. Unfortunately, that "fortunate coincidence" may instead be a test of Jethri's loyalties, as he's thrust into a tangle of gray-trading, mistaken identity, misinformation, and galactic politics. . . "--